1986
DOI: 10.3181/00379727-182-42361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium and Vitamin E Dietary Deficiencies on Chick Lymphoid Organ Development

Abstract: Diets specifically deficient in selenium (Se) and/or vitamin E or adequate in both nutrients were fed to chicks from the time of hatching. Lymphoid organs (bursa, thymus, and in some instances, spleen) were collected from chicks 7-35 days of age. Growth of the chicks fed these diets was monitored over the experimental period as was lymphoid organ growth. The development of the primary lymphoid organs was further assessed by histological techniques and the organ contents of vitamin E (a-tocopherol) and Se were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…In addition, vitamin E along with selenium has been found to be essential for the proper growth and development (Marsh et al, 1986) and for the overall immunocompetence of growing broilers. However, use of these medicinal plants or feed additives in diets of broiler chicken with the objectives of improving their performance and hematological parameters status has not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitamin E along with selenium has been found to be essential for the proper growth and development (Marsh et al, 1986) and for the overall immunocompetence of growing broilers. However, use of these medicinal plants or feed additives in diets of broiler chicken with the objectives of improving their performance and hematological parameters status has not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with Peng et al (2009) andEl-Sheikh et al (2010), who reported that selenium plays a significant role in the development of bursa of Fabricius. Marsh et al (1986), Hegazy and Adachi (2000) and Hussain et al (2004) found that lymphoid organs (bursa of Fabricius, spleen and thymus) size of birds fed lower selenium diet content was significantly lower than birds fed higher selenium diet levels.…”
Section: Discussionmentioning
confidence: 99%
“…Judging by the findings of Marsh et al (1986) on the susceptibility of the bursa of Fabricius in chicks, we might anticipate an antibody failure in animals with Se deficiency, but other work by the same group (Marsh et al 1981) has shown that this depends on age: 2-week-old chicks kept on Se-or Se-vitamin E-deficient diets from hatching all showed reduced titres to SRBC, whereas in animals only 1 week older, only the Se-vitamin E-deficient group was disadvantaged (Table 1). Se-deficient mice given 50 pg vitamin E/g diet showed reduced IgG but normal IgM responses to SRBC, suggesting that it is the helper T-dependent class switch which is particularly vulnerable to a Se deficiency.…”
Section: A N T I B O D Y P R O D U C T I O Nmentioning
confidence: 99%
“…In Se-vitamin E-deficient chicks, the thymus and bursa both showed reduced numbers of lymphocytes, preceded by damage to the surrounding epithelia (Marsh et al 1986). This suggests that the normal flow of inductive signals from epithelial cells to the developing lymphocytes is not occurring.…”
mentioning
confidence: 99%
See 1 more Smart Citation